How Is Bovine Genital Leptospirosis Diagnosed Under Field Conditions? - Juliana Pedrosa; Julia Mendes; José Zambrano; Filipe Aníbal Carvalho-Costa; Maria Isabel Nogueira Di Azevedo; Luiza Aymée; Walter Lilenbaum (Animals)
Bovine genital leptospirosis (BGL) is a chronic reproductive disease in cattle, often causing significant economic losses, and is commonly associated with leptospiral strains belonging to the Sejroe serogroup. A two-step protocol was recommended, based on serological screening of the herds followed by an individual diagnosis with PCR of a genital sample. Although proposed, it has not been commonly applied under field conditions, leading to frustrating outcomes in disease control. In that context, the present study aimed to demonstrate the viability of that two-step protocol under field conditions for diagnosing BGL in eight herds with reproductive disorders. Blood samples were collected from 440 cows for serology. In addition, 304 cervicovaginal mucus (CVM) samples were collected for lipL32-PCR and 11 samples were sequenced of the secY gene. All herds showed high seroreactivity, mainly against the serogroup Sejroe. In addition, 113 of the 304 CVM samples (37.2%) were PCR-positive. DNA sequencing of 11 positive samples based on the secY gene revealed maximum identity (100%) with L. interrogans species. This study found CVM sampling quick and easy, making it practical for field use. Overall, the results support the two-step protocol serological screening followed by CVM-PCR testing as an efficient and reliable method for diagnosing BGL in herds with reproductive disorders in field conditions.